2007
DOI: 10.1111/j.1467-9280.2007.01948.x
|View full text |Cite
|
Sign up to set email alerts
|

For Whom the Mind Wanders, and When

Abstract: An experience-sampling study of 124 undergraduates, pretested on complex memory-span tasks, examined the relation between working memory capacity (WMC) and the experience of mind wandering in daily life. Over 7 days, personal digital assistants signaled subjects eight times daily to report immediately whether their thoughts had wandered from their current activity, and to describe their psychological and physical context. WMC moderated the relation between mind wandering and activities' cognitive demand. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
335
6
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 827 publications
(426 citation statements)
references
References 38 publications
34
335
6
2
Order By: Relevance
“…The frequency of mind wandering was lower than in research on its frequency in daily life (Kane et al, 2007;Kane et al, in press;Killingsworth & Gilbert, 2010;Marcusson-Clavertz et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The frequency of mind wandering was lower than in research on its frequency in daily life (Kane et al, 2007;Kane et al, in press;Killingsworth & Gilbert, 2010;Marcusson-Clavertz et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…The average person spends as much as a third of their waking life engaging in thought that is unrelated to the current activity (Kane et al, 2007;Kane et al, in press;Marcusson-Clavertz, Cardeña, & Terhune, 2016), a phenomenon known as mind wandering (Schooler et al, 2011;Smallwood & Schooler, 2015). Evidence suggests that during mind wandering, one's attention is coupled to task-independent thoughts and concomitantly dissociated from perceptual input, resulting in an attenuation of sensory processing (perceptual decoupling; (Barron, Riby, Greer, & Smallwood, 2011;Smallwood, Beach, Schooler, & Handy, 2008).…”
Section: Public Significance Statementmentioning
confidence: 99%
“…During this period of idleness, we found that internally generated momentary ruminative self-referent thoughts were causally influenced by the cognitive capacity to regulate negative mental representations in WM, associated with DLPFC neural activation. In fact, it has already been shown that increased WM performance relates to decreased mind wandering during daily life (e.g., Kane et al, 2007;McVay & Kane, 2010), and even predicts the regulation of thought and behavior (Kane & Engle, 2003). Indeed, an enhancement of the executive-control system to adequately combat interfering thoughts that are generated and maintained automatically, is related to decreased ruminative self-referent thoughts (McVay & Kane, 2010 , which states that cognitive control processes play a central and causal role in the relation between prefrontal neural activation and rumination.…”
Section: Discussionmentioning
confidence: 99%
“…Its prototypical psychological signature features low arousal (Smith & Ellsworth, 1985;cf. Goetz, Frenzel, Hall, Nett, Pekrun, & Lipnevich, 2014), a lack of perceived meaning and challenge in the activity at hand (Van Tilburg, Igou, & Sedikides, 2013), mind-wandering (Kane, Brown, McVay, Silvia, Myin-Germeys, & Kwapil, 2007), low attention (Eastwood et al, 2012), and the desire to change the current activity or to disengage from it (Van Tilburg & Igou, 2012).…”
Section: From the Fringes Towards The Mainstreammentioning
confidence: 99%
“…Boring activities can lead to mind-wandering (Kane et al, 2007), or "stimulusindependent thought" (Killingsworth & Gillbert, 2010), due to a lack of engaging taskfeatures that should sustain a person's attention (Eastwood et al, 2012). To be clear, although boredom may often lead to mind-wandering, a wandering mind may not necessarily feel bored, for example when people daydream (Schupak & Rosenthal, 2009).…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%